Molecular dynamics study of uncharged bupivacaine enantiomers in phospholipid bilayers - Martini, María Florencia (2012)
To investigate the effects of the uncharged bupivacaine (BVC) on the properties of model membranes of 1-palmitoyl- 2-oleoyl-sn-glycero-3-phosphatidylcholine (POPC), we have performed a series of molecular dynamics simulations. A very particular characteristic of the local anesthetic BVC, that is being discuss in the recent literature, is that their enantiomers R-(þ) (R-BVC) and S-(À) (S-BVC) present different activities. In this way, we have studied both enantiomers in a POPC phospholipids bilayers at a high molar ratios [local anesthetic (LA):lipid of 1:3]. The simulations were able to capture important features of the BVC?phospholipid bilayer interactions: BVC molecules are found in the interior of the bilayer. The R-BVC enantiomerfollows a bimodal distribution with access to the water?lipid interface; while the S-BVC is found, in more uniformdistribution, at the hydrophobic region. A decrease in theacyl chain segment order parameters, SCD, compared to neatbilayers, is found. Furthermore, this behavior is morenoticeable for the R-BVC form. The found decrease in SCD isattributed to a larger accessible volume per lipid in the tailregion. Our results could help to understand the highertoxicity of this enantiomer.